PENGARUH AKUNTABILITAS PENGELOLAAN KEUANGAN DANA DESA DAN PEMBERDAYAAN MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT NAGARI KECAMATAN LINTAU BUO SUMATERA BARAT - Edri, Ollavia; Yusrawati,; Siska, (Journal Of Islamic Finance And Accounting Research, 2022)
This study aims to determine the effect of accountability for village fund financial management and community empowerment on the welfare of the Nagari community, Lintau Buo District. This research is a descriptive study with a quantitative approach, using multiple linear regression analysis using SPSS version 16. The population in this study were all Nagari Devices and Community Leaders in Lintau Buo District and sampling using purposive sampling technique with 44 respondents. The results of the test are that the accountability of village fund financial management has a positive and significant effect on the welfare of the Nagari community and community empowerment positively and significantly on the welfare of the Nagari community.